The Students Experience of Hybrid- Education Model at The University of Baghdad College of Pharmacy - Ahmed, Kawther Khalid; Al-Jumaili, Ali Azeez; Salman, Salema Sultan; Kathem, Sarmed Hashem (Iraqi Journal of Pharmaceutical Sciences, 2021)
The impact of COVID-19 pandemic on education models was mainly through the expansion of technology use in the different educational programs. Earlier impact of COVID-19 was manifested in the complete and sudden transition to distance education regardless of institution preparedness status. Gradually, many institutions are moving back to on-campus face-to-face education. However, others including all higher education institutions in Iraq are adopting the hybrid education model. This report presents part of the end of semester evaluation survey conducted at the University of Baghdad College of Pharmacy for the Spring 2021 semester. The survey aims to address points of strength and weakness associated with the hybrid education model and specifically the virtual content delivery aspect of hybrid education. The outcomes of the end of semester evaluation will shape a better experience for upcoming years and guide distance education implantation in the program.